Notch Blockade Specifically in Bone Marrow-Derived FSP-1-Positive Cells Ameliorates Renal Fibrosis - Yongdong Wu; Ming Liang; Fengzhang Huang; Owen H. Cheng; Xiaoguang Xiao; Tae Hoon Lee; Luan Truong; Jizhong Cheng (Cells, 2023)
Background: The infiltration of inflammatory cells during a kidney injury stimulates myofibroblast activation leading to kidney fibrosis. Fibroblast-specific protein 1 (FSP-1) positive cells have been reported as either myofibroblasts or monocytes during tissue fibrosis. The functions of FSP-1+ cells that are associated with the development of renal fibrosis and the signaling pathways that regulate FSP-1+ cell activation have not been well defined. Methods: In mice with unilateral ureteral obstruction (UUO), we characterized FSP-1+ cells and determined the role of the Notch signaling pathway in the activation of bone marrow-derived FSP-1+ cells during kidney fibrosis. Results: In kidneys from mice with UUO, the FSP-1+ cells accumulated significantly in the tubulointerstitial area. By using immunostaining and FSP-1 reporter mice, we found that FSP-1 was co-stained with inflammatory cell markers, but not myofibroblast markers. Results from mice with bone marrow transplantations showed that FSP-1+ cells in obstructed kidneys represent a bone marrow-derived population of inflammatory cells. In cultured FSP-1+ cells, the inhibition of Notch signaling suppressed the activation and cytokine secretion of FSP-1+ cells that were induced by LPS but not by IL-4. The specific KO or blockade of Notch signaling in bone marrow-derived FSP-1+ cells suppressed UUO-induced ECM deposition, the infiltration of FSP-1+ inflammatory cells, and cytokine production. These responses ameliorated myofibroblast accumulation and renal fibrosis in obstructed kidneys. Conclusion: Our study reveals that most FSP-1+ cells in obstructed kidneys are activated macrophages that are derived from bone marrow and that Notch signaling activates the production of M1 cytokines in FSP-1+ monocytes/macrophages, which is important for renal inflammation and fibrosis.